Relationship Between Spot Prices and Futures Prices: Evidence From Karachi Stock Exchange - Muhammad Asif Ali; Muhammad Asif Ali; Dr. Naveed Hussain Shah (Journal of Business & Tourism, 2021)
This study investigates the relationship between futures prices and their underlying spot prices of the stocks trading on Pakistan stock market. Data on the monthly closing prices of future contracts and their underlying stocks of 30 companies for the period January 2004 to June 2014 have been taken for analysis. Descriptive statistics, Augmented Dicky Fuller test for unit root testing, Johnson Co-integration test, Granger causality test and Vector Error Correction Model are used. The results confirms significant long term relationship between futures prices and the associated Spot prices in case of 26 companies. The report of Granger causality test indicates that a Bi-directional causality lack to exist in case of each security, VECM shows that Spot prices for current month are effected by previous month prices in case of 7 companies, while futures prices of current month are affected by previous month prices in case of 4 companies. VECM illustrates that the volatility shocks in spot market are less effected by futures market, however the volatility shocks in corresponding futures market were strongly and significantly affected by spot market volatility.